The effects of beetroot juice supplementation on balance performance of wrestlers - Tatlici, Ali; Lima, Yavuz; Yılmaz, Sercan; Ekin, Abdulkadir; Okut, Sedat (LAHORE MEDICAL RESEARCH CENTER LLP, 2021)
Aim: This study assessed the effect of beetroot juice supplementation on the dynamic and static balance performance of wrestlers at rest and fatigue conditions. Material and methods: The study was conducted with 3 trial days. The study is a double-blind, randomized, crossover design in which eight trained male Greco-Roman wrestlers (age 21.87 +/- 2.3 years; height 176.87 +/- 4.1 cm; body weight 76.75 +/- 5.4 kg) consumed beetroot juice (BRJ) (140 ml) or placebo (PLA) (140 ml, cherry juice with lemon juice) 150-min before performing balance performance test. Subjects were administered standard warm-up and then dynamic and static balance tests were performed to the dominant leg with by Biodex Balance System (BBS, Biodex Medical Systems Inc., Shirley, NY) at rest. Following balance testing, each subject got into a fatigue strength exercise (FSE) to create fatigue for the dominant leg. Immediately after the (FSE), subjects were applied to dynamic and static balance test to the dominant leg again at fatigue. The same trial procedure was repeated with the other supplement (BRJ or PLA) in the third testing trial five days later. Paired sample T-test was used for comparison of BRJ and PLA balance performance values. Result: Although there were no significant changes in static OSI, APSI balance scores, Static MLSI improved significantly in favor of BRJ in rest. Dynamic OSI and APSI parameters improved significantly but not MLSI in the BRJ trial. While all static and dynamic balance parameters improved statistically, only static MLSI was not changed by the BRJ trial at fatigue. Conclusion: Consuming BRJ can be useful to maintain balance performance and prevent sports injuries in training or competition. Keywords
Keywords: Beetroot JuiceDietary; Nitrate; Balance; Wrestlers